The role of eco-digital learning in enhancing the impact of IoT, blockchain, and artificial intelligence on green supply chain for SME internationalization - Faisol; Hestin Sri Widiawati; Risky Aswi Ramadhani; Bambang Agus Sumantri (Problems and Perspectives in Management)
The study aims to analyze the moderating role of eco-digital learning for the impact of the Internet of Things, blockchain, and artificial intelligence on the green supply chain to support SME internationalization. Questionnaires were distributed among 159 SME owners in Kediri, East Java, Indonesia. Hypotheses were tested using PLS-SEM. The results indicate that the adoption of the Internet of Things demonstrates a significant positive effect (p = 0.0000, T-statistic = 4.6695), improving real-time monitoring and operational efficiency. Blockchain also positively affects SME internationalization (p-value = 0.0085, T-statistic = 2.6427), enhancing supply chain transparency and ensuring compliance with international standards. In contrast, the influence of artificial intelligence is marginally significant (p = 0.0799, T-statistic = 1.7548), constrained by financial limitations and lack of expertise. The moderating effects of eco-digital learning show mixed results. It significantly moderates the relationship between the Internet of Things and internationalization in a negative direction (coefficient = –0.0651, p = 0.0475), suggesting that increased eco-digital learning may add complexity, potentially delaying the benefits of the Internet of Things. For blockchain, eco-digital learning enhances its positive impact (p = 0.0277, T-statistic = 2.2085) by strengthening the organization’s ability to leverage transparency and sustainability. However, no significant moderating effect is observed for artificial intelligence (p = 0.2066, T-statistic = 1.2646), indicating limited integration due to resource constraints. These findings highlight the importance of technological readiness, resource allocation, and alignment of digital learning to fully capitalize on the benefits of these technologies in the global market expansion of SMEs. AcknowledgmentsDeepest gratitude is extended to the Ministry of Education and Culture, Directorate of Research, Technology, and Community Service (DRTPM), for the financial support provided through the National Competitive Research Program under the “Regular Fundamental Research” scheme for the 2024 fiscal year. This support was instrumental in enabling the successful completion of this research.